The Role of Auditor Characteristics on Tax Avoidance - Hendi, Hendi; Sherly, Sherly (Universitas Kristen Maranatha, 2024)
Abstract Purpose - This study aims to explore the role of auditor characteristics on the practice of tax avoidance in Indonesia. Auditor characteristics are determined from the auditor industry specialization, audit opinion, audit tenure, and audit fee. Meanwhile, tax avoidance behavior is determined from a comparison of the effective tax rate (ETR). Design/methodology/approach - The secondary data analysis on this study applies a panel data regression method to analyze data from companies listed on the Indonesia Stock Exchange between 2018 and 2022. Findings - The findings indicate that audit tenure has a significant negative effect on tax avoidance. Meanwhile, auditor industry specialization, audit opinion, and audit fees do not have a significant effect on tax avoidance. Research limitations/implications - The results of this study contribute to the role of auditor characteristics on tax avoidance practices. Keywords: Auditor Characteristics, Audit Fee, and Tax Avoidance